The effects of setting conditions of trash bins on waste collection performance and waste separation behaviors; distance from walking path, separated setting, and arrangements. (1st July 2019) - Leeabai, Nattapon; Suzuki, Shinya; Jiang, Qiuhui; Dilixiati, Dilinazi; Takahashi, Fumitake
Graphical abstract: Highlights: Trash bins were studied in terms of waste collection performance. Longer distance out of walking path decreased combustible waste collection. The distance gave no impact on waste separation and foreign waste mixture. Separating setting of trash bins decreased waste separation efficiency. Trash bin arrangement gave no change on waste collection and separation. Abstract: This study investigated the effects of setting conditions of trash bins on waste collection, separation efficiency, and incorrect disposal. Tested trash bins are for combustible wastes, PET bottles, cans, and glass bottles. Monitoring results were analyzed by statistical tests to distinguish real effects and experimental errors. The distance to trash bins along walking path gave no significant effects on waste collection and the others. On the other hand, when the distance was out of walking path, its increase significantly decreased waste collection of combustible wastes. In contrast, the distance gave no significant effect on separation efficiency and foreign waste percentage. It was suggested that threshold distance that affects waste disposal behaviors is between 8 and 410 m. When trash bins were set separately, it affected the motivation of waste separations. Separated setting of combustible waste and PET bottle trash bins in the opposite side of the original position significantly decreased separation efficiencies of these wastes. Because no significant effect was found on separation efficiency of other wastes whose trash bins were set in the original position, additional 3 m distance to the opposite side might exceed the threshold distance and have caused low separation efficiencies. The preference of trash bin arrangement gave no significant effect on waste collection and the others excluding separation efficiency of can. These results suggest that appropriate location of trash bins can improve waste collection and waste separation. It might be useful for waste management in public areas with high population density like shopping mall.